State history, intergenerational transmission and institutional trust in Africa - Gian Luca Tedeschi (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
This research advances the hypothesis that intergenerationally transmitted beliefs act as a mechanism through which pre-colonial institutions influence modern day attitudes towards state figures in African countries. To address the question empirically, I combine contemporary individual-level survey data with historical data on precolonial political centralisation by ethnic group. By employing an identification strategy based on the current location of individuals and the disease environment of the ethnic groups' historical homelands, I establish that individuals belonging to ethnic groups that were characterised by a pre-colonial state show significantly higher levels of trust in current day institutions.
Keywords: O10; O43; Z10; Z13; 330; Pre-colonial institutions; intergenerational transmission; trust; cultural persistence; Africa